Rôle de la Végétation sur la stabilité de l’érosion hydrique et qualité des sols sur les piémonts nord du Dahra Ouest de Mostaganem Commune de Sidi Ali - HADID, Warda; SELLAKH, Nour El Houda (My University, 2017)
The present study was conducted in the farmland of Douar Ouled Naimia, northern Sidi Ali (Mostaganem), where water erosion is becoming important. It is a serious threat for agricultural soils, which can influences, badly, the productivity. The objective of this study is to develop a methodology using geographic information systems (GIS) to model qualitatively, by using the model Bachoui (2007), The determination of the risks of hydric erosion and zones sensitive to high risk in the zone of study will be of use to the establishment of a card of the risks allowing the authorities by a development plan to intervene quickly before the situation deteriorates. Because the ground is a not renewable heritage which it is absolutely necessary to protect to keep it in state to produce enough and healthily for the future generations.
Keywords: Farmland; hydrous erosion; GIS; sensibility; risk; Terres agricoles; érosion hydrique; SIG; sensibilité; risques